The Epidemiology of Facial Trauma Presentations during and after the Implementation of COVID-19 Social Distancing Measures—The Coventry-Warwickshire (UK) Experience. (September 2021) - McEwen, Ellie C.; Hoffman, Gary R.; Qiu, Michael M.; Pandya, Rishi; Walton, Gary M.
Purpose: The COVID-19 pandemic resulted in the institution of strict public health measures aimed at reducing virus transmission. This coincided with a well-documented alteration to the frequency and characteristics of maxillofacial trauma presentations. The aim was to examine the incidence and characteristics of maxillofacial trauma at a large tertiary hospital in the United Kingdom to determine whether these previously reported changes persisted after the relaxation of COVID-19 "lockdown" legislation.Method: This was a retrospective cohort study of patients who sustained a facial injury during the 8-week period of 16th March 2020 to 11th May 2020 (strict COVID lockdown) compared to the 11th May 2020 to 6th July 2020 (relaxation of COVID lockdown). Cohorts were compared on the incidence and characteristics of facial injury.Results: Compared to the peak of COVID-19 lockdown, the subsequent period during which these laws were eased saw an increase in the frequency of maxillofacial trauma presentations (n = 78 vs n = 37). Despite this absolute increase, the incidence remained statistically below seasonal expectation. Operative management remained persistently low (45% in 2020 vs 67% in 2019).Conclusion: This is the first study to report the characteristics of facial trauma after the easing of COVID-19 lockdown legislation. Compared to previously published reports from Australia, there has not yet been a clear return to baseline epidemiology in the UK, perhaps reflecting the severity of the pandemic in that region.